281. Cefdinir Prescribing Increased in Low-Income Children in Kentucky From 2012 to 2016. (26th November 2018) - Smith, Michael; Vidwan, Navjyot; Wattles, Bethany; Ghosal, Soutik; Feygin, Yana; Creel, Liza; Myers, John; Woods, Charles
Abstract: Background: Cefdinir is frequently prescribed to pediatric outpatients with respiratory infections despite a lack of first-line indications. The use of cefdinir should be limited given its poor efficacy against Streptococcus pneumoniae, suboptimal pharmacokinetic and pharmacodynamic parameters, and high cost. We describe cefdinir use over time in the pediatric Kentucky (KY) Medicaid population including rates of use, associated diagnoses, and cost to the Medicaid system. Methods: We reviewed KY Medicaid pharmacy and medical claims from 2012 to 2016 for all patients <20 years of age. Cefdinir prescriptions were identified by national drug codes and linked to medical claims within 3 days prior to the prescription date. Diagnoses were classified into the following groups by ICD9 and ICD10 codes: acute otitis media (AOM), sinusitis, pharyngitis, lower respiratory infections, and urinary tract infections. Upper respiratory infections (URIs) commonly caused by viruses (e.g., nasopharyngitis, bronchitis, cough) were categorized as presumed viral infections. Cost data were extracted from pharmacy claims. Cochran-Armitage was used to test for trends across the study period. Results: Cefdinir prescriptions significantly increased from 60, 334 (8% of all antibiotic prescriptions) in 2012 to 99, 053 (13% of all antibiotic prescriptions) in 2016 ( P < 0.001). Cefdinir use in rate per 1, 000 children increased from 195 in 2012 to 294 in 2016. Medicaid spending on cefdinir increased from 2.3M (15% of all antibiotic spending) in 2012 to 4.7M (27% of all spending) in 2016. Eighty-eight percent of pharmacy claims for cefdinir had an associated medical claim within 3 days prior to prescription. Indications associated with cefdinir are summarized in Figure 1. Three groups accounted for the majority of cefdinir use: AOM, presumed viral infections, and pharyngitis. Conclusion: Outpatient cefdinir use in pediatric patients served by KY Medicaid significantly increased over the study period. Much of this use was inappropriate. Antibiotics are not useful against viral infections, which accounted for 23% of cefdiniruse. When antibiotics are indicated for bacterial URI, agents with better pneumococcal coverage are preferred. Preventing overuse of this costly, broad-spectrum antibiotic is an important focus for antimicrobial stewardship efforts. Disclosures: All authors: No reported disclosures.